Focus meets motivation: When regulatory focus aligns with approach/avoidance motivation in creative processes - Mühlberger, Christina; Endrejat, Paul; Möller, Julius; Herrmann, Daniel; Kauffeld, Simone; Jonas, Eva (Frontiers in Psychology, 2022)
According to Regulatory Focus Theory, two systems determine our strategies to pursue goals – the promotion and the prevention system. Individuals with a dominant promotion system focus on achieving gains, i.e., promoters, and individuals with a dominant prevention system focus on avoiding losses, i.e., preventers. Regulatory Fit Theory suggests that a fit between this focus and the situation causes superior performance and makes individuals feel right. We transfer the fit idea to the interaction of dominant regulatory focus (promotion vs. prevention) with motivational direction (approach vs. avoidance motivation). We investigated these interaction effects on individuals’ performance and their experience within creativity workshops. In Study 1 (N1 = 172), using multi-level analyses, we found that a promotion focus was associated with fluency and a prevention focus with elaborated ideas. This effect was stronger, when preventers also scored high on avoidance motivation. Further, preventers experienced more autonomy support and were more satisfied when they scored high on avoidance. Promoters high on approach motivation reported more autonomy support and more satisfaction than preventers high on approach motivation. For Study 2 (N2 = 112), we used an experimental design: After measuring regulatory focus, we manipulated approach vs. avoidance motivation in creativity workshops. Using multi-level analyses, we did not find main or interaction effects on fluency or elaboration but we found interaction effects on participants’ experience of the creativity workshop. Preventers were more satisfied when they received the avoidance condition. Promoters reported less autonomy support, lower satisfaction, and more perceived conflicts within their teams in the avoidance condition.